1999
DOI: 10.1007/s001250051273
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glucose transport and protein kinase Cβ 2 in rat skeletal muscle induced by hyperglycaemia

Abstract: Skeletal muscle is quantitatively the most important tissue involved in maintaining glucose homeostasis, accounting for about 80 % of glucose disposal after a glucose infusion or ingestion [1]. Glucose transport is the rate-limiting step for glucose metabolism in insulin sensitive tissues [2,3]. In skeletal muscle, glucose transport is mediated by a process involving the translocation of glucose transporters (GLUT), namely GLUT4, from an intracellular site to the plasma membrane [4,5]. Glucose transporter 4 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 56 publications
5
25
1
1
Order By: Relevance
“…We previously reported that high glucose concentrations interact in a dual way with the insulin signalling cascade; hyperglycaemia induced translocation of GLUT4 in three different muscle-derived model systems [17] and hyperglycaemia induced insulin resistance in rat-1 fibroblasts [19]. In agreement with this, several studies reported an hyperglycaemia-induced increased glucose uptake [18,20]. In this study, we found such an effect on GLUT4 translocation in whole, insulin-resistant animals.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We previously reported that high glucose concentrations interact in a dual way with the insulin signalling cascade; hyperglycaemia induced translocation of GLUT4 in three different muscle-derived model systems [17] and hyperglycaemia induced insulin resistance in rat-1 fibroblasts [19]. In agreement with this, several studies reported an hyperglycaemia-induced increased glucose uptake [18,20]. In this study, we found such an effect on GLUT4 translocation in whole, insulin-resistant animals.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously reported that the PKC isoform b is important for the short-term high glucose effect in muscle [17]. Hyperglycaemia has been shown to induce translocation of PKC-bI and -bII [20]. However, the effect on PKCbI failed to reach statistical significance in the latter study.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations